2014
DOI: 10.1007/s00380-014-0606-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors and left ventricular function in patients with slow coronary flow

Abstract: Slow coronary flow (SCF) is characterized by delayed distal vessel opacification in the absence of significant epicardial coronary disease. Life-threatening arrhythmias and sudden cardiac death can occur; however, the pathological mechanism and influence on left ventricular function remain undetermined. We aimed to assess the risk factors and left ventricular (LV) function in SCF and evaluate the relationships between thrombolysis in myocardial infarction frame count (TFC) and the number of involved coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
2
10
1
1
Order By: Relevance
“…Conventional Doppler imaging (CDI) is commonly used to evaluate LV diastolic function . Previously, it was shown that CSF is related to LV diastolic dysfunction . Similar to these studies, we showed decreased E velocity, increased A velocity, a decreased E/A ratio, and a prolonged IVRT and isovolumic contraction time in CSF patients using CDI.…”
Section: Discussionsupporting
confidence: 87%
“…Conventional Doppler imaging (CDI) is commonly used to evaluate LV diastolic function . Previously, it was shown that CSF is related to LV diastolic dysfunction . Similar to these studies, we showed decreased E velocity, increased A velocity, a decreased E/A ratio, and a prolonged IVRT and isovolumic contraction time in CSF patients using CDI.…”
Section: Discussionsupporting
confidence: 87%
“…20,27 Coronary slow flow is a condition characterized by the slowing down of coronary artery flow rate, and is defined as delay in the filling of epicardial coronary arteries with contrast agent without the existence of stenosis. 30 The underlying mechanisms and aetiology remain unknown, however, studies have shown that endothelial dysfunction, vasomotor dysfunction, microvascular disease and generalized atherosclerosis may play a role in aetiopathogenesis. [31][32][33][34] In patients with coronary slow flow, studies have identified lengthwise extensive calcification without narrowing the lumen, diffuse intimal thickening, and atheroma plaques in the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…These data collectively confirm a strong relationship between LVEF impairment and the risk of slow flow after RA. Previous studies have indeed indicated that coronary flow is closely related to both systolic and diastolic LV function and that slow coronary flow is more frequent in patients with LV dysfunction [20, 21]. It is worth noting that the operators in our study did not react with glycoprotein IIb/IIIa inhibitors to slow-flow events possibly because of concomitant higher bleeding risks in the cohort with bad ventricular function.…”
Section: Discussionmentioning
confidence: 51%